2004
DOI: 10.1002/bit.20294
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of cell mixtures using acoustic and laminar flow fields

Abstract: A fractionation method applicable to different populations of cells in a suspension is reported. The sepa ration was accomplished by subjecting the suspension to a resonant ultrasonic field and a laminar flow field propa gating in orthogonal directions within a thin, rectangular chamber. Steady, laminar flow transports the cell suspen sion along the chamber, while the ultrasonic field causes the suspended cells to migrate to the mid-plane of the chamber at rates related to their size and physical proper ties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…From An obvious application of this ability to segregate and focus particles in channels is flow cytometry, where current approaches that employ sheath flows or dielectrophoresis to hydrodynamically focus cells into a narrow line within the fluidic channel require ample quantities of consumables to generate sheath flow or a planar geometry for all but the latest dielectrophoretic methods (Cheng et al, 2007). A relatively early study by Kumar et al (2005) reported the acoustic separation of hybridoma and lactobacillus using ultrasound irradiation perpendicular to the main axis of flow, with modest efficiency and flow rate. Goddard and Kaduchak (2005) used ultrasound to focus 10 m particles and cells in a 190 mm long glass capillary tube with an inner diameter of 1.9 mm along a 14 mm long region exposed to acoustic radiation at 417 kHz from a pair of PZT transducers attached to either side of the tube.…”
Section: In Closed Environmentsmentioning
confidence: 99%
“…From An obvious application of this ability to segregate and focus particles in channels is flow cytometry, where current approaches that employ sheath flows or dielectrophoresis to hydrodynamically focus cells into a narrow line within the fluidic channel require ample quantities of consumables to generate sheath flow or a planar geometry for all but the latest dielectrophoretic methods (Cheng et al, 2007). A relatively early study by Kumar et al (2005) reported the acoustic separation of hybridoma and lactobacillus using ultrasound irradiation perpendicular to the main axis of flow, with modest efficiency and flow rate. Goddard and Kaduchak (2005) used ultrasound to focus 10 m particles and cells in a 190 mm long glass capillary tube with an inner diameter of 1.9 mm along a 14 mm long region exposed to acoustic radiation at 417 kHz from a pair of PZT transducers attached to either side of the tube.…”
Section: In Closed Environmentsmentioning
confidence: 99%
“…The position of the piezoelectric material with respect to the device determines which type of configuration the resonator is in. There are three main configurations where the piezoelectric material can be placed against the chip which are transversal [61,92,107,94], layered [82,108,85,109] and surface acoustic wave (SAW) configurations [87][88][89]. In the transversal configuration, the piezoelectric material is placed on the device such that the standing wave is positioned along an axis perpendicular to the normal of the piezoelectric patch surface.…”
Section: Hardwarementioning
confidence: 99%
“…ACT methods have been implemented for bio-particle wash [95,47,96,84,125,92], trapping [125,92,[126][127][128][129][130][131][132][133][134] and separation [69,108,85,91,9,81,135,94,136,137]. Bio-particle washing relies on focusing the particles to the center of the channel, and out flowing the bio-particles collected at the center into another suspension medium.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, particles are initially aligned to a starting position within a flow chamber using a sheath flow 14,31,32 , or an acoustic pre-alignment stage 33 , then deflected under the action of the sorting acoustic field which can be excited using bulk axial 28 , bulk lateral 29 , or surface acoustic wave excitation 16 . It can be shown 34 that in the low Reynolds number regime typically found in this work, particles reach their terminal velocity within a matter of milli-seconds.…”
Section: Hydrodynamic Forcesmentioning
confidence: 99%